Applications of Blockchain Technology to Higher Education Arena: A Bibliometric Analysis - Reis-Marques, Carlos (2021)
Reis-Marques, C., Figueiredo, R., & Neto, M. D. C. (2021). Applications of Blockchain Technology to Higher Education Arena: A Bibliometric Analysis. European Journal of Investigation in Health, Psychology and Education, 11(4), 1406-1421. https://doi.org/10.3390/ejihpe11040101 ---------------------------------------------- This work is financed by national funds through FCT—Fundação para a Ciência e a Tecnologia, I. P., under the project “UIDB/04630/2020”.